Viral load in symptomatic and asymptomatic patients infected with SARS-CoV-2. What have we learned? - Mozgovoj, Marina Valeria; Dieder Graham, Merceder; Ferrufino, Cecilia; Blanc, Sofia; Fernandez Souto, Adriana; Pilloff, Marcela; Dus Santos, Maria Jose (Elsevier, 2024)
Asymptomatic and presymptomatic patients played a critical role in the maintenance and spread of infection during COVID pandemic. However, conflicting views about the infectiousness of asymptomatic patients have been raised.